PENGARUH KOMPETENSI, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU PADA SEKOLAH DASAR SE-KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT - Husaini, Husaini; Saiful; Sari (IndOmera, 2024)
The aim of the research is to determine and prove the influence of teacher competency, work motivation and job satisfaction factors on teacher performance both partially and simultaneously. This research is in the form of a survey with quantitative associative descriptive methods. With analytical tools using a multiple regression analysis approach. The research was conducted in 30 elementary schools involving 215 elementary school teacher respondents in Johan Pahlawan Meulaboh sub-district, West Aceh Regency. The research results found (a). The level of achievement of teacher competence is in the good category, namely 88.08%, the level of achievement of teacher work motivation is high at 82.08%, while the level of teacher satisfaction at work has reached 84.33% and the level of achievement of teacher competence is in the good category. Teacher performance is good, reaching 84.86% of ideal expectations. (b) The results of multiple regression analysis conclude that the factors of teacher competence, work motivation and teacher satisfaction partially have a positive effect on performance, (c). Based on correlation and determination analysis, it is proven that there is a very close relationship and the three factors, namely teacher competence, work motivation and teacher satisfaction, contribute 53.5% to changes in teacher performance